2014
DOI: 10.5614/itbj.ict.res.appl.2014.8.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 3 Key Factors on Average End to End Delay and Jitter in MANET

Abstract: A mobile ad-hoc network (MANET) is a self-configuring infrastructure-less network of mobile devices connected by wireless links where each node or mobile device is independent to move in any desired direction and thus the links keep moving from one node to another. In such a network, the mobile nodes are equipped with CSMA/CA (carrier sense multiple access with collision avoidance) transceivers and communicate with each other via radio. In MANETs, routing is considered one of the most difficult and challenging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 8 publications
1
6
0
2
Order By: Relevance
“…In MANETs, routing is a difficult task due to the changes in network topology, making it difficult to select a particular protocol. Several studies have focused on comparing protocols, paying less attention to other factors such as packet size, node mobility, Direct Sequence Spread Spectrum (DSSS) rate and the mobility pattern, among others [29]. Therefore, it is essential to determine the importance of these factors for network functioning.…”
Section: Experiments Desing Using 2 K Factorialmentioning
confidence: 99%
See 2 more Smart Citations
“…In MANETs, routing is a difficult task due to the changes in network topology, making it difficult to select a particular protocol. Several studies have focused on comparing protocols, paying less attention to other factors such as packet size, node mobility, Direct Sequence Spread Spectrum (DSSS) rate and the mobility pattern, among others [29]. Therefore, it is essential to determine the importance of these factors for network functioning.…”
Section: Experiments Desing Using 2 K Factorialmentioning
confidence: 99%
“…Therefore, it is essential to determine the importance of these factors for network functioning. In [29] the authors consider three factors: the routing protocol (Dynamic MANET On-demand (DYMO) and Ad hoc On-Demand Distance Vector (AODV)), packet size, and DSSS rate. These factors influence the average delay and the average jitter, which are network performance factors that affect the buffering requirements for video devices and downstream networks [29].…”
Section: Experiments Desing Using 2 K Factorialmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same work various parameters of network performance (routing protocol, node density, node speed, traffic load, and pause time) are considered to analyze the factors and interactions for the network performance of DSR and AODV routing protocols by determining various metrics (packet delivery ratio, average delay, discovery time, and recovery time) using a factorial design. Many other works used factorial design to quantify the main and interactive effects [11,10,12,13]. The authors in [14], have used a factorial design technique to analyze routing mobile ad-hoc networks and have developed two first-order linear models that define the relationship between the influential parameters and two performance metrics.…”
Section: Related Workmentioning
confidence: 99%
“…Through the simulation study they have found that the LAR protocol reduces the energy consumption. The performance of DYMO and AODV protocol using QualNet simulator have been analyzed by Hakak et al [18]. They have performed the simulation study using 100 nodes with random waypoint mobility model with the max speed 30 mps.…”
Section: Related Workmentioning
confidence: 99%